2008
DOI: 10.1175/2008jhm981.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Characteristics of Snowpack Density in the Mountainous Regions of the Western United States

Abstract: Snow density is calculated as a ratio of snow water equivalent to snow depth. Until the late 1990s, there were no continuous simultaneous measurements of snow water equivalent and snow depth covering large areas. Because of that, spatiotemporal characteristics of snowpack density could not be well described. Since then, the Natural Resources Conservation Service (NRCS) has been collecting both types of data daily throughout the winter season at snowpack telemetry (SNOTEL) sites located in the mountainous areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
85
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 27 publications
7
85
2
Order By: Relevance
“…We found low spatial variability in density that showed no significant relationship with elevation at our sites. This observation concurs with other studies of mountain snowpacks finding spatial consistency in the density of mountain snowpacks (Jonas et al, 2009;Mizukami and Perica, 2008).…”
Section: Ground Measurementssupporting
confidence: 93%
“…We found low spatial variability in density that showed no significant relationship with elevation at our sites. This observation concurs with other studies of mountain snowpacks finding spatial consistency in the density of mountain snowpacks (Jonas et al, 2009;Mizukami and Perica, 2008).…”
Section: Ground Measurementssupporting
confidence: 93%
“…While SWE is the primary variable of interest for hydrologic applications, snow depth is a key variable for avalanche forecasting [20]. Because snow density is generally less variable in space than snow depth [67,68], knowledge of snow depth distribution can also potentially be converted to SWE via empirical regressions [69] or dynamic models [62]. In this context, portable, low-cost techniques, such as UAS and a MS, can fill an important gap between laborious, manual measurements and large-scale surveys at lower resolution using satellites or manned aircrafts.…”
Section: Discussionmentioning
confidence: 99%
“…At the basin scale, an approach to reducing the sampling effort is to use snow depth as a surrogate for SWE by developing a model for snow density, as manual snow density measurements require more time and effort than snow depth measurements. Recent studies have attempted to characterize the spatiotemporal characteristics of snow density (e.g., Mizukami and Perica, 2008;Fassnacht et al, 2010), or to develop reliable methods for modeling snow density and thus estimating SWE from snow depth measurements (e.g., Jonas et al, 2009;Sturm et al, 2010).…”
Section: G a Sexstone And S R Fassnacht: What Drives Basin Scale mentioning
confidence: 99%
“…At operational sites, the seasonal variability of snow density is largely dictated by time of year, and interannual variability is typically low (Mizukami and Perica, 2008). However, previous spatial snow surveys have shown that snow density can exhibit inter-annual variability, particularly in continental regions (e.g., Balk and Elder, 2000;Jepsen et al, 2012).…”
Section: Snow Density Modelmentioning
confidence: 99%
See 1 more Smart Citation